Million dollar demon eaudiobook - Harrison, Kim (The Hollows, 2021)
To save the city, Rachel Morgan will need to show some teeth in the next Hollows novel from #1 New York Times bestselling author Kim Harrison. The new master vampire of Cincinnati has arrived . . . and she wants Rachel Morgan out. No matter where Rachel goes, Constance is there—threatening Rachel's allies, causing city-wide chaos, and, to add insult to injury, even forcing Rachel out of her current quarters. Ever since Rachel found a way to save the souls of vampires, the old undead's longtime ascendancy has been broken. Now Constance sees eliminating Rachel as the key to consolidating her own power. Rachel has no desire to be enthralled or killed—and she's terrified of what may become of the city if Constance forces a return to the ancient ways. But even a witch-born demon can't stand against the old undead—at least, not alone. And if Rachel refuses to claim the role of Cincinnati's master demon, the city will tear itself apart, taking her and all those who stand beside her with it.